Prospecção, identificação e atividade antifúngica de proteínas de sementes de Fabaceae da Amazônia brasileira - Brito, Daniel de (2018)
The Amazon Forest is seen as one of the main focus of global biodiversity, and it represents the most complex ecosystem of the planet. Historically, the daily use of forest species by traditional populations, for the most diverse purposes, has attracted the researchers’ attention. However, the scientific study of forest species has its challenges. To overcome the difficulties of territorial access/ exploration, seasonality of the climate, and the intrinsic characteristics of each species strongly restrict the prospecting and systematic studies. This work was planned in response to an initiative of the Federal Government (CAPES) that stimulated the biological prospecting in the Brazilian Amazon. Focused on plant seeds, the study aimedto investigate proteins in native species. After botanical collection, fifty species of the Fabaceae family were selected for study. Seed proteins were extracted in saline and the extracts were tested in a growth inhibition assays of the following phytopathogenic fungi: Aspergillus sp., Aspergillus flavus, Aspergillus niger, Fusarium sp., Fusarium oxysporum, Penicillium chysogenum and Phomopsis sp. Extracts belonging to species that were identified as endemic of the Brazilian Amazon [Dimorphandra caudate, Dimorphandra parviflora (Caesalpinieae); Swartzia longistipitata, Swartzia recurva (Swartzieae); Zygia trunciflora (Ingeae)] were further evaluated by SDS-PAGE, proteomic analysis by mass spectrometry (MS/MS) of selected spots, and prospected for enzymatic activities of proteases and chitinases. Protein fractionation through ion exchange matrices allowed the partial purification of a lectin and three chitinases which were evaluated for their antifungal activities and mechanism of action. The antifungal activity of the extracts was widely observed among the tested fungi and was most representative in the Ingeae tribe. Proteases, chitinases and protease inhibitors were identified in the samples and chitinolytic activity was predominant. Fluorescence microscopy assays demonstrated the binding of propidium iodide to DNA of Fusarium oxysporum spores, suggesting that spore integrity was lost when exposed by the partially purified proteins. It was observed that the protein extracts of the seeds collected in the Amazon had a strong antifungal action and that chitinase activity was associated with this effect. These findings may be good subsidies for further molecular study of these seed chitinases from endogenous plants and their defense activities, considering that the seeds of 15 these plants are subjected to a complex set of adversities inherent to the Amazonian ecosystem, especially to the fungal attack when they fall on the ground and germinate.